1993
DOI: 10.1021/bi00091a032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of two substrate analogs on thermodynamic properties of medium-chain acyl-CoA dehydrogenase

Abstract: The objective of this work was to identify the key structural functionalities of substrate or product that modulate the thermodynamic properties of medium-chain acyl-CoA dehydrogenase (MCAD). In order to achieve this, two classes of substrate analogues, acetyl-CoA and thioether-CoAs, were complexed with MCAD and their effects on the redox properties of MCAD were measured. A pH dependence study of the redox potential of uncomplexed MCAD allowed us to compare redox properties between complexed and uncomplexed MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 41 publications
2
44
0
Order By: Relevance
“…From this finding, it can be concluded that the redox potential, E 1 , of the E-Fl ox /E-FlH • couple is more negative than E 2 , the E-FlH • /E-Fl red H -couple. The values for E 1 and E 2 cannot be estimated because of the small amount of semiquinone thermodynamically stabilized (<5%), which is substantially less than the 20% found for pig kidney MCADH under similar conditions (24). The redox potential determined for hwtMCADH (-0.114 V) is an average of E 1 and E 2 , and is thus best described as a midpoint potential.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…From this finding, it can be concluded that the redox potential, E 1 , of the E-Fl ox /E-FlH • couple is more negative than E 2 , the E-FlH • /E-Fl red H -couple. The values for E 1 and E 2 cannot be estimated because of the small amount of semiquinone thermodynamically stabilized (<5%), which is substantially less than the 20% found for pig kidney MCADH under similar conditions (24). The redox potential determined for hwtMCADH (-0.114 V) is an average of E 1 and E 2 , and is thus best described as a midpoint potential.…”
Section: Discussionmentioning
confidence: 84%
“…For the purpose of comparison, the E m vs pH dependence of pig MCADH obtained at 25°C (24) has been reanalyzed using the same equation as with hwtMCADH. The results indicate some marked differences.…”
Section: Characterization Of Recombinant Hwtmcadhmentioning
confidence: 99%
“…Assuming that there is only a small change in redox potential of the individual flavins on formation of the ETF⅐MCAD complex, ⌬G for electron transfer from hydroquinone MCAD to oxidized ETF (Ϫ0.12 eV) and from semiquinone MCAD to oxidized ETF (Ϫ0.16 eV) was calculated from the known potentials of the semiquinone/hydroquinone (Ϫ94 mV) and oxidized/semiquinone (Ϫ134 mV) couples of MCAD (at pH ϭ 7.1 (36)) and the potential of the oxidized/semiquinone couple (ϩ22 mV) of human ETF (37). The reorganization energy, , was set to 0.7 eV.…”
Section: Methodsmentioning
confidence: 99%
“…This behavior has been exhibited by other acyl-CoA dehydrogenases such as the short and medium chain acyl-CoA dehydrogenases (SCAD and MCAD). Through spectroelectrochemical studies of SCAD and MCAD, where each were complexed with different substrate, product, and substrate and product analog compounds, it was revealed that the electron transfer behavior of these enzymes is regulated by the binding of certain CoA compounds in the active site (2,3,4,5). The particular substrate analog syntheses reported here were designed to supply analogs that should bind to the GCD active site, enabling GCD spectroelectrochemical studies similar in design to those for SCAD and MCAD to be performed.…”
mentioning
confidence: 99%